2017
DOI: 10.5539/jfr.v6n5p22
|View full text |Cite
|
Sign up to set email alerts
|

Diet Induced Modifications of Fatty-Acid Composition in Mealworm Larvae (Tenebrio molitor)

Abstract: The diet of Western human societies is characterized by an excess of saturated fatty acids (FAs) and a high concentration of ω-6 relative to ω-3 polyunsaturated FA (PUFA). These unbalanced diets are suspected to trigger diseases and disorders. To alleviate this public health concern, the production of healthier meat with more PUFAs of higher ω-3 concentration could potentially be achieved by modifying livestock diets. The high nutritional value and limited breeding costs of edible insects have brought insect f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 37 publications
(34 reference statements)
3
15
1
Order By: Relevance
“…Insects have a very relevant plasticity to modulate body fat composition. The main factor influencing it is the substrate in which the larvae are grown [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Insects have a very relevant plasticity to modulate body fat composition. The main factor influencing it is the substrate in which the larvae are grown [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Low amounts of eicosenoic acid and vaccenic acid have been reported in yellow mealworm larvae by Ravzanaadii et al [9]. Fasel et al [19] studied the fatty acid composition of yellow mealworm larvae after feeding them different ratios and concentrations of ω-3/ω-6 FA. They concluded that the larvae possess plasticity to convert FA into triglycerides, and therefore changes in dietary lipids could be reflected in the FA composition of the larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the last years, several farms and food-feed companies worldwide have started to employ this insect. Nutritional composition of mealworm larvae revealed a relatively high content of protein, 50% on a dry-matter basis [11,12], and lipids, about 30%–34% on a dry-matter basis [12,13,14], with a good composition in amino acids (good source of the essential amino acids), vitamins (i.e., vitamin E, vitamin B12, niacin, riboflavin, pantothenic acid, and biotin), and minerals (P, K, Mg, Zn, and Mn) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Few research studies were carried out on the rearing conditions and on the effects of different substrates on the development and chemical-biological characteristics of mealworm larvae [7,10,13,14,16,17]. Most of the cited studies highlighted a plasticity of T. molitor in relation to the substrate, with variations of both development times and nutritional values of the larvae.…”
Section: Introductionmentioning
confidence: 99%